2015
DOI: 10.5897/jmpr2014.5744
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and cytotoxic activity of black and green tea from Vaccinium meridionale Swartz leaves

Abstract: Tea is a beverage made from leaves with high contents of polyphenolic substances that vary based on the process they are subjected to. In this study, the apical and young leaves from Vaccinium meridionale (named mortiño) were processed to obtain two kinds of tea: green and black tea. This was done in order to compare their antioxidant activity, content of secondary metabolites at different temperatures of extraction and their antiproliferative effect against SW480 colon cancer cells. Results showed that at 40°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In both methods it is noted that the results for FRAP assay decreases with the leaves moisture content; in the case of infrared drying shown in Figure 4a, its results were from 0.5 to 6 mg equivalent ascorbic acid/g dry leaves, which are lower than the ones obtained by microwave drying (see Figure 4b) (10-50 mg equivalent ascorbic acid/g dry leaves). It is assumed, based on the literature, that total phenols previously quantified are responsible for iron (III) reduction to iron (II) measured in this assay (Zapata-Vahos et al, 2015). This confirms that there is a better availability of the labile hydrogen proportion in polyphenols inside the dried leaves by microwave than in the ones dried by infrared.…”
Section: Antioxidant Capacity Assayssupporting
confidence: 80%
See 2 more Smart Citations
“…In both methods it is noted that the results for FRAP assay decreases with the leaves moisture content; in the case of infrared drying shown in Figure 4a, its results were from 0.5 to 6 mg equivalent ascorbic acid/g dry leaves, which are lower than the ones obtained by microwave drying (see Figure 4b) (10-50 mg equivalent ascorbic acid/g dry leaves). It is assumed, based on the literature, that total phenols previously quantified are responsible for iron (III) reduction to iron (II) measured in this assay (Zapata-Vahos et al, 2015). This confirms that there is a better availability of the labile hydrogen proportion in polyphenols inside the dried leaves by microwave than in the ones dried by infrared.…”
Section: Antioxidant Capacity Assayssupporting
confidence: 80%
“…The UV-visible spectrum was from 200 to 600 nm for all peaks. The compound's identification and quantification were done with the calibration curves for each one of the analytes desired (Zapata-Vahos et al, 2015).…”
Section: Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds were detected in the plant species evaluated in this study, therefore, it is presumed that the antioxidant activity of their extracts is related to these substances. However, it can not be ruled out that flavonoids can act by reducing the oxidation rate in synergism with other phenolic compounds and not only attribute this property to this constituent, as verified by Zapata-Vahos et al (2015).…”
Section: Resultsmentioning
confidence: 99%
“…Antioxidants and polyphenols, being polar bioactive compounds (Figueroa et al, 2018;Gaviria Montoya et al, 2012;Oteiza et al, 2005), are sensitive to the effect of microwaves as mentioned above (Mejia-Meza et al, 2010;Śledź et al, 2013), and for that reason, the change in their antioxidant concentration due to the drying of the leaves requires a search for optimal operating conditions which allow verifying that the content of antioxidants and polyphenols is taken at the end of the drying process (Kwok et al, 2004;Madrau et al, 2009;Rabeta & Vithyia, 2013). To carry out the study of the effect of drying on the measurement of antioxidants and polyphenols at the beginning and the end of the process (Haytowitz & Bhagwat, 2010;Wijewickreme & Kitts, 1997), analytical techniques can be used such as the ferric-reducing/antioxidant power (FRAP) and total phenols (TP), reported in the literature as techniques that value the antioxidant capacity (Garzón et al, 2010;Prior et al, 1998;Wanyo et al, 2010;Wojdyło et al, 2009); and in turn, instrumental techniques such as high-performance liquid chromatography with diode-array detection (HPLC-DAD) were used to identify and quantify the presence of catechin molecules (Melgar et al, 2018;Tremocoldi et al, 2018;Wang et al, 2008a;Wang et al, 2008b); these molecules had already been reported by authors in previous writings (Gaviria et al, 2009;Isabel et al, 2015;Maldonado-Celis et al, 2014).…”
Section: Introductionmentioning
confidence: 94%